Student's inquiry skills and learning achievement in plant anatomy practical work using open-guided inquiry - Setiono, S; Rustaman, N Y; Rahmat, A; Anggraeni, S (Journal of physics. Conference series, 2019)
The important of inquiry based learning (IBL) had been investigated, but not the inquiry skills as fundamental skills for students, especially prospective teachers. This descriptive study was carried out to get illustration about the inquiry skills and their knowledge from practical open-guided inquiry in plant anatomy practical works. A number of prospective biology teachers in second semester was involved as participants (n=23). Data were collected through the use of certain instruments to detect inquiry skills and concept mastery got from IBL practical activities. Research results show that the prospective biology teachers can achieve score on inquiry skills as well as concept mastery above the minimum score determined previously (75). IBL laboratory experienced by prospective biology teachers can debrief their inquiry skills and help them in constructing knowledge they need in science instruction.